Effectiveness of Teams Games Tournament Cooperative Learning with Wordwall Educational Games on Similarity - Grace Angel Rhena Saragih; Ade Mirza; Nurfadilah Siregar; Hamdani Mikraj; Dian Ahmad Budhysatrya (SJME (Supremum Journal of Mathematics Education), 2026)
This research seeks to investigate the effectiveness of integrating the TGT cooperative learning model with Wordwall-based educational games in enhancing students' conceptual understanding of similarity at SMP Abdi Agape Pontianak. A pre-experimental approach was adopted in this study, utilizing a one-group pretest-posttest design, with 28 Grade VII A students selected as the sample. The instruments consisted of tests, questionnaires, and observation sheets, generating data in the form of test results, questionnaire responses, and students' levels of engagement obtained from the observation sheets. The data were analyzed using descriptive and inferential statistical techniques. The findings indicated that the implementation of this approach was effective, as it met the predetermined effectiveness indicators, namely students mathematics learning outcomes reached the KKTP of ≥ 65, the classical mastery level was  , the improvement in learning outcomes was  , student responses met the positive criteria of , and learning activities met the active criteria of . This effectiveness is supported by hypothesis testing results where the average learning outcome was > 64,9, classical completeness was > 74,9, average learning gain was > 0.3 or moderate category, student responses rated as very positive at 81,47%, and student activity was rated as very active at 95%. This study shows that the TGT cooperative learning model assisted by Wordwall educational games is effective because it meets all indicators of learning effectiveness, including minimum mathematics learning outcomes, classical mastery, meaningful learning improvement, positive student responses, and student activity during the learning process.